Integrating ISA Server 2006 with Microsoft Exchange 2007 - Strachan, Fergus (Burlington, MA. : Syngress, 2008)
This book is a convenient, targeted, single-source guide to integrating Microsoft's ISA Server with Exchange 2007 SP1. Unlike longwinded "comprehensive resources" it doesn't waste time re-hashing general information on the architectures and purposes of ISA and Exchange for raw beginners. Instead, its pragmatic purpose is to smooth the path of the busy administrator who is under pressure to get the integration done quickly, and done right, the first time. It features "break-out sessions" for issues that require in-depth discussion, "tips and tricks" sections that hone in on and demystify trouble spots, and "FAQs" alphabetized by topic that act as a quick-reference for readers who just want a quick answer to a specific question. Readers will learn how to: *Create the protocol definitions and firewall policy to allow only authorized users to connect to your Exchange Server *Configure SMTP Filtering and SMTP Message Screener *Troubleshoot the SSL connection to your Exchange Server *Take advantage of ISA 2006's integrated Exchange 2007 support *Enable forms-based authentication for Outlook Web Access *Leverage unified SSL, VPN, application-layer filtering and endpoint security to optimize access for mobile devices *Configure user-based settings to provide pre-authenticated access to specific Web applications ... and much more! *Practical and focused, this guide explains explains everything you need to know in order to successfully integrate ISA 2006 and Exchange 2007, without wasting time on minutiae *Tips and tricks from the expert author help you avoid pitfalls before you stumble into them, troubleshoot problems with ease, and optimize performance *In-depth coverage of Exchange SP1 highlights the many security enhancements that optimize integration with ISA.
Introduction -- Why ISA and Exchange? -- Exchange 2007 SP1 Updates Supporting ISA -- SP1 Enhanced Disaster Recovery Features -- ISA 2006 Essential Integration Issues -- Configure SMTP filtering and SMTP Message Screener -- Publish a Microsoft Outlook Web Access server -- Secure Outlook Client Connections -- Enabling Certificates -- Troubleshooting Web Connections -- Optimization.
Includes index.
Keywords: Microsoft ISA server; Microsoft Exchange server; Firewalls (Computer security); Client/server computing; Computer networks -- Security measures; Electronic books